Ketika Masyarakat Mengadili: Studi sosiologi Hukum tentang Praktik Hukuman Sosial di Era Digital - Lidia Theresia Rotua Simamora (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The phenomenon of social punishment has become increasingly widespread today due to the growing use of social media as a space for interaction among the public. In the digital sphere, people can instantly impose social sanctions by posting comments, sharing news, forming collective opinions, and engaging in â€œcancel cultureâ€ against individuals perceived to have violated norms. These events often occur beforeâ€”or even withoutâ€”the formal legal processes that should serve as the legitimate means of resolving disputes. This study aims to analyze various forms of digital social punishment, the social and cultural factors that drive these mechanisms, and the impact of this phenomenon on public perceptions of the legitimacy and effectiveness of formal law. Using a socio-legal perspective, this research highlights the role of society as an informal enforcer of norms and examines how interactions on digital platforms shape new modes of norm application. The analysis shows that social punishment in the digital era can strengthen normative awareness and promote respect for the law, but it can also lead to issues such as stigma, injustice, and online judgments lacking verified information. These findings emphasize the need for greater alignment between informal social control mechanisms and the formal legal system to create balance in the application of norms within digital society.